Muscular Hypertrophic Effects of Oral Contraceptive Consumption in Women - Pinheiro, João Augusto Recliski; da Silva, Luiz Augusto; Weber, Vinicius Muller Reis; Malfatti, Carlos Ricardo Maneck; Brasil, Marcos Roberto (Journal of Pharmacy and Nutrition Sciences, 2023)
Hormones have several actions in the body; among their effects on effector organs, they can control the volume of skeletal muscle. The excess of hormones, in this case exogenous ones, could be altering the effects of physical exercise on skeletal muscle hypertrophy, especially after the consumption of contraceptives. Thus, we have a general objective in this work to evaluate the effects of contraceptive consumption on hypertrophy in women. We sought an integrative literature review with studies within 2001-2021, using the PubMed and Scielo databases. Seven articles were selected for a complete and coherent reading for the development of this review. Given the studies analyzed in the present study, it was possible to observe that the effects of oral contraceptives may indeed influence muscle hypertrophy. However, it can assist in preserving soft tissues, avoiding the looseness of the anterior cruciate ligament (ACL). For individuals aiming to enhance lean muscle mass, particularly in high-performance contexts, it is advisable to consider alternative contraceptive methods that do not disrupt the natural hormonal system. In conclusion, the OC user group did not obtain significant gains in lean mass, but their levels of dehydroepiandrosterone (DHEA), sex hormone agglobulinal ligand (SHBG), and insulin-like growth factor (IGF1) decreased, with increasing levels of only cortisol. Thinking of high performance to increase lean muscle mass, another means of contraceptives that do not affect the physiological hormonal system should be used.